Astrocyte-Derived Interleukin 11 Modulates Astrocyte–Microglia Crosstalk via Nuclear Factor-κB Signaling Pathway in Sepsis-Associated Encephalopathy - Dandan Zhu; Peng Wang; Xiyue Chen; Kaituo Wang; Yunsong Wu; Min Zhang; Jianhua Qin (Research)
Sepsis-associated encephalopathy (SAE) is a severe and frequent septic complication, characterized by neuronal damage as key pathological features. The astrocyte–microglia crosstalk in the central nervous system (CNS) plays important roles in various neurological diseases. However, how astrocytes interact with microglia to regulate neuronal injury in SAE is poorly defined. In this study, we aim to investigate the molecular basis of the astrocyte–microglia crosstalk underlying SAE pathogenesis and also to explore the new therapeutic strategies targeting this crosstalk in this devastating disease. We established a human astrocyte/microglia coculture system on a microfluidic device, which allows real-time and high-resolution recording of glial responses to inflammatory stimuli. Based on this microfluidic system, we can test the responses of astrocytes and microglia to lipopolysaccharide (LPS) treatment, and identify the molecular cues that mediate the astrocyte–microglia crosstalk underlying the pathological condition. In addition, the SAE mouse model was utilized to determine the state of glial cells and evaluate the therapeutic effect of drugs targeting the astrocyte–microglia crosstalk in vivo. Here, we found that activated astrocytes and microglia exhibited close spatial interaction in the SAE mouse model. Upon LPS exposure for astrocytes, we detected that more microglia migrated to the central astrocyte culture compartment on the microfluidic device, accompanied by M1 polarization and increased cell motility in microglia. Cytokine array analysis revealed that less interleukin 11 (IL11) was secreted by astrocytes following LPS treatment, which further promoted reprogramming of microglia to pro-inflammatory M1 phenotype via the nuclear factor-κB (NF-κB) signaling pathway. Intriguingly, we found that IL11 addition markedly rescued LPS-induced neuronal injuries on the microfluidic system and brain injury in the SAE mouse model. This study defines an unknown crosstalk of astrocyte–microglia mediated by IL11, which contributed to the neuropathogenesis of SAE, and suggested a potential therapeutic value of IL11 in the devastating disease.